In vitro cytotoxicity of methanol extracts of Hypericum wightianum and Hypericum hookerianuim against 3T3L1 cell lines - Narayanan Ravisankar; Joseph Jerrine; Manikkan Radhakrishana; Thirunavukkarasu Rajasekar (Bangladesh Pharmacological Society, 2016)
No abstract is available